A new approach to modal decomposition of buckled shapes. (November 2015) - Becque, Jurgen; Li, Xilin
Abstract: The paper proposes a novel methodology to construct the individual local, distortional, and global buckling modes of a thin-walled structural element under a given loading. The resulting buckling modes form an orthogonal basis of the deformation space, so that any random deformed shape can be expressed as a linear combination of the basic buckling modes. The method is applicable to open branched or unbranched cross sections, as well as cross sections containing closed parts. Examples are provided to illustrate the procedure.